2012
DOI: 10.1063/1.4745015
|View full text |Cite
|
Sign up to set email alerts
|

Local structure, paramagnetic properties, and porosity of natural coals: Spectroscopic studies

Abstract: Using methods of the scanning electron microscopy, Raman scattering of light(RS), and electron paramagnetic resonance (EPR), consistent research of the local structure and magnetic features of different types of raw coal samples from Donetsk basin is carried out. It is established that the ratio of the main peak intensities of RS spectrum D and G is inversely related to the volatile substance amount Vdaf in the coal samples. The study of the kinetic behavior of the EPR line width in hydrogen, oxygen, and metha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…The results show that the anthracite conductivity is strongly dependent on temperature and on the material origin [6,8]. The particular one, studied by us, the temperature dependency of which is seen in Fig.…”
Section: Electrical Conductivitymentioning
confidence: 91%
See 3 more Smart Citations
“…The results show that the anthracite conductivity is strongly dependent on temperature and on the material origin [6,8]. The particular one, studied by us, the temperature dependency of which is seen in Fig.…”
Section: Electrical Conductivitymentioning
confidence: 91%
“…Various authors [9][10][11][12] pointed out that the conduction electrons should contribute to the EPR signal intensity of electrically conducting coals. Sometimes, the narrow component of the EPR spectra were attributed to these conduction electrons [8,13]. However, the Curie-type temperature dependency of the signal intensity suggested that most of the centers were localized [14].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…The structure of coals is an irregular polymer like matrix, which consists of the structural elements of different nature: aromatic, aliphatic, and heterocyclic fragments and carbon clusters between them [4][5][6][7][8][9]. The chemical composition and rank of coals are responsible for the mutual arrangement of fragments and porous structure peculiarities.…”
mentioning
confidence: 99%